ANALYSIS OF THE LEVEL OF AEROBIC ENDURANCE (VO2MAX) ON THE PERFORMANCE OF BANDUNG CITY HOCKEY ATHLETES - Shobirin Shobirin; Alen Rismayadi; Yudi Nurcahya (Universitas Negeri Medan, 2023)
Aerobic endurance level (VO2max) is an important part of a hockey athlete's performance. It is very important to reduce fatigue and fatigue when playing, while it can be an advantage in game tactics. Therefore, the purpose of this researcher is to prove that there is a relationship between the level of aerobic endurance (VO2max) and the performance of hockey athletes. This research method uses descriptive quantitative with correlation technique research design. The sample used was 24 Bandung City hockey athletes including 12 male athletes and 12 female athletes and, sampling using total sampling techniques. The instruments used are the Multistage Fitness Test and GPAI (Game Performance Assessment Instrument) for the performance level of hockey athletes. The results of the study analyzed using the Spearman's Rho test on SPSS stated that the data from the average value of the aerobic endurance level (VO2max) of room hockey was 50.00 with a standard deviation value of 10.01 and the lowest score was 37.52, the highest score was 65.82 and the total score was 1200. Meanwhile, the average value of athlete performance is 0.77 with a standard deviation value of 0.074 and the lowest score of 0.67, the highest score of 0.94 and a total score of 18.40. The correlation coefficient of the two variables is unidirectional which is positive 0.567 in the interpretation of moderate correlation. So the results of this study there is a relationship between the level of aerobic endurance (VO2max) on the performance of hockey athletes.